إشكاليَّات دور مجلس الأمن في ظل الشرعيَّة الدوليَّة الجديدة بعد أحداث الحادي عشر من أيلول 2001 - ناصوري أحمد; المصري خالد; أبو حسن حمزة (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يدرس البحث إشكاليَّات دور مجلس الأمن في ظل الشرعيَّة الدوليَّة بعد أحداث الحادي عشر من أيلول للعام 2001، ويهدف هذا البحث إلى مقاربة ظاهرة الشرعيَّة الدوليَّة مع التركيز على موقع مجلس الأمن بالنسبة إليها باعتبار قراراته تشكل مصدراً من مصادر هذه الشرعيَّة. كما سيدرس البحث ذلك التَّراجع الذي لحق بالشرعيَّة الدوليَّة في ظل النظام الدولي أحادي القطبيَّة، ذي النَّزعة التدخليَّة، التي عمَّقتها أحداث أيلول، بما أفرزته من تداعيات انعكست في الدرجة الأولى في تفاعلات النظام الدولي ذاته، والتي كان من جملتها تهميش دور الأمم المتحدة الذي انعكس بصورة مباشرة على أداء مجلس الأمن وعلى دوره في نظام الأمن الجماعي مُبرزاً جملة من الإشكاليَّات اتضحت في ممارسات المجلس ذاته بشكل انحرافات واضحة، لاسيما لجهة اتخاذ الدول العربيَّة ميداناً رئيساً لتجريب أدواره الجديدة وتفعيل سلطاته وصلاحيَّاته بعد انفراد الولايات المتحدة الأمريكيَّة بالهيمنة على الساحة الدوليَّة بعد نهاية الحرب الباردة وتجذر هذا التفعيل بعد أحداث أيلول، التي أخرجت الشرعيَّة الدوليَّة عن سياقها الطبيعي ليتجاوز مجلس الأمن دوره الأصيل كأداة رئيسة لتنفيذ قرارات الشرعيَّة الدوليَّة بثلاثيَّة: تنشيط الفصل السابع من ميثاق الأمم المتحدة، توسيع مفهوم "تهديد السلم والأمن الدوليين"، وانحسار حالات الاختصاص الداخلي للدول، مُبرزاً إلى الوجود ضعف الشرعيَّة الدوليَّة الجديدة. The following research studies the problematic issues of the Security Council’s role in light of International Legitimacy after the events of September 11, 2001. It aims to approach the International Legitimacy phenomenon with a focus on the position of Security Council in relation to such an approach, as its decisions constitute a source of this legitimacy. This research also considers that decline of International Legitimacy in light of unipolar international system that is characterized by the tendency of interference deepened by the events of September 11, including the repercussions which were primarily reflected in reactions of the international system itself. One of these repercussions was the marginalization of the UN’s role and its direct effect on the performance of the Security Council and its role in the collective security system. This had brought out a number of dilemmas which became clear in the Council practices which took the form of apparent deviations, especially in terms of making Arab states a major arena for testing its new roles, activating its authorities and powers after the U.S. took the lead in dominating the international arena after the end of the Cold War, and deepening such activation after the events of September 11. All these has brought the International Legitimacy out of its natural context; thus, the Council exceeds its original role as a means to implement international legitimacy resolutions with a trilogy: Activating Chapter VII of the UN Charter, expanding the concept of "threat to international peace and security" and the decline of the domestic jurisdiction of States; thus, bringing out the weakness of the new International Legitimacy.